STUDI LITERATURE PERAN MEDIA INTERAKTIF DALAM PEMBELAJARAN IPAS KELAS 4 SD - Hasani, Baitil; Yasin, Fajar Nur; Jannah, Amilah Uzlifatul; Aprilia, Devi Nurrochmah; Anam, Nur Sirojil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This article discusses the role of interactive media in learning Natural and Social Sciences (ESS) for grade 4 students through literature study method. The research shows that interactive media, such as videos, digital simulations and technology-based quizzes, can improve the quality of learning by making the learning process more dynamic, interesting and effective. It facilitates students' understanding of complex concepts, increases learning motivation, and supports project-based learning that is relevant to the IPAS curriculum. In addition, interactive media creates a collaborative learning environment, provides flexibility in learning time, and provides real-time formative feedback. However, the implementation of this media faces challenges such as limited technological infrastructure and lack of teacher training. To overcome these obstacles, collaboration between the government, schools and related parties is needed. With the right support, interactive media can help students develop 21st century skills, such as critical thinking, collaboration and digital literacy. This article concludes that interactive media has an important role in improving the effectiveness of IPAS learning, making it more relevant and in line with the needs of the digital era.